Legal status of the Kyrgyz tribes in the administrative and legal device of the Russian Empire (the second half of 19 century – the beginning of 20 century) (Journal of actual problems of jurisprudence, 2019)
This article is disclosing an issue of legal status of Kyrgyz tribes within administrative governance of Russian Empire.The work provides with some facts from the history of accession of Kyrgyz tribes into Russian Empire. Particularattention is paid to the discussion of legal reforms that were conducted after accession to the Russia.Key words: legal status, customary law, «erezhe», governor of volost, governor of aul, volost and aul congress.